2019
DOI: 10.14309/01.ajg.0000596140.06597.7d
|View full text |Cite
|
Sign up to set email alerts
|

1653 Large Cell Neuroendocrine Carcinoma of the Colon

Abstract: INTRODUCTION: Neuroendocrine carcinomas heterogeneous group of tumors with variable clinical presentation and prognosis. Gastrointestinal neuroendocrine carcinomas are further divided into two types; small cell or large cell based on mitotic rate and or Ki-67 labeling by WHO or European Neuroendocrine Tumor Society guidelines. Large cell neuroendocrine carcinomas (LNEC) of primary colorectal origin are extremely rare and represent 0.25% of all colorectal cancers. LNEC are malignant and aggressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bernick et al publish a study that showed that 0.6% of patients with malignant colorectal tumors had neuroendocrine carcinoma and only 0.2% of those were large cell neuroendocrine carcinomas [ 6 ]. There is paucity of paper reporting large cell colonic neuroendocrine carcinomas (LCNEC) in literature [ [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…Bernick et al publish a study that showed that 0.6% of patients with malignant colorectal tumors had neuroendocrine carcinoma and only 0.2% of those were large cell neuroendocrine carcinomas [ 6 ]. There is paucity of paper reporting large cell colonic neuroendocrine carcinomas (LCNEC) in literature [ [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%